Simplified patient positioning to reduce beam hardening in CT of the lower neck. - Harvey, G D; Mayer, D P; Radecki, P D (American Journal of Neuroradiology, 1984)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf